1926 Va. Acts. 285-87, ch. 158, §§ 1-9. - (:unkn) unknown (General Publisher, 1926)
Be it enacted by the general assembly of Virginia, That it shall be the duty of every person residing in this State and owning a pistol or revolver therein, to pay on or before the first day of January of each year a license tax of one dollar on each pistol or revolver so owned, or in the event that such pistol or revolver shall be acquired by any such person on or after the first day of February, such license tax shall be forthwith paid thereon.
--
Keywords: TAX - PROPERTY OR SALES